A história da licenciatura em enfermagem na Universidade de Caxias do Sul: um olhar para as práticas docentes (1974-2001) - Oliveira, Cássio de (My University, 2021)
This project is part of the Post-Graduation Programme in Education of the University of Caxias do Sul (UCS), Brazil, in the History and Philosophy of Education area. The purpose of this research was to analyze the teaching practices in the training of nurses at UCS, between the years 1974 - 2001, based on the educational policies of the institutional and regional contexts. In Brazil, the Nursing Licentiate Course was created by Decree No. 837/68, which originated the Decree by the Ministry of Education and Culture (MEC) No. 13/69, which granted the title of educators for nurses, to help training more high-school level healthcare workers (nursing auxiliaries and technicians). At the University of Caxias do Sul Foundation (FUCS), the Nursing Licentiate course was created on May 5, 1974, through Resolution No. 1.074 of the FUCS Council of Teaching, Research and Extension, and recognized through of Ordinance No. 90, of January 21, 1980. The research conduction was of qualitative nature, anchored by the precepts of Cultural History, based on Pesavento (2014) and Chartier (1990; 1991). For the construction of the History of School Disciplines, Chervel (1990) and Viñao (2008) were used as references. The methodological option was based on Oral History, as it allows the researcher and the interviewees to (re)signify the subjectivity found in every word, as defended by scholars such as Alberti (2013), Portelli (2016), and Meihy and Barbosa (2019). The empiric corpus is made of document sources obtained at the UCS Institute of Historical and Cultural Memory (IMHC). The interviews with licensees totaled ten and were based on a previously defined script. From the interviews, categories and subcategories were established, which were analyzed from the perspective of Content Analysis, as proposed by Roque Moraes (1999; 2003). Three of them stood out with greater relevance in the speeches, due to contributions and knowledge arising from the degree; disciplines and methodologies used in the classroom; and the degree as professional registration permission according to MEC, a "teacher's card". The theoretical foundation for the categories was based on Tardif (2014) and Tardif and Lessard (2014), with an explanation of professional knowledge and teaching practices; Anastasiou and Alves (2015), with assumptions for work strategies in the classroom, Nóvoa (1995; 1999; 2009; 2011), with the concepts of teacher learning and teachers' professional development. The study allowed for the discussion of the historical foundations of the training of nursing professionals in higher education, in addition to the explanation and analysis of the objectives and proposals of the political-pedagogical projects. Thus, the research allowed the understanding that nursing has had, since the beginning of its creation as a profession, the aspect of being a practical tool, but always linked to issues related to education. Thus, it is understood that it was possible to contemplate the initial proposal of the research, because in addition to access to documentary sources, there was a considerable effort by the researcher to build a possible narrative about the history of the Nursing Degree course at UCS, through the memories of people who experienced that educational context. [resumo fornecido pelo autor]
A presente investigação foi realizada junto ao Programa de Pós-Graduação em Educação, da Universidade de Caxias do Sul, vinculada à linha de pesquisa História e Filosofia da Educação, e buscou analisar as práticas docentes vivenciadas na formação do enfermeiro licenciado na UCS entre os anos de 1974 e 2001, à luz das políticas educacionais, do contexto institucional e regional. No Brasil, o Curso de Licenciatura em Enfermagem foi criado pelo Parecer no 837/68, que deu origem à Portaria do Ministério da Educação e Cultura (MEC) no 13/69, concedendo o título de licenciado ao enfermeiro, para atender à exigência social de formação profissional de nível médio (auxiliares e técnicos de enfermagem). Na Fundação Universidade de Caxias do Sul (FUCS), por sua vez, o curso de Licenciatura em Enfermagem foi criado em 05 de dezembro de 1974, por meio da Resolução no 1.074 do Conselho de Ensino, Pesquisa e Extensão da FUCS, e reconhecido por meio da Portaria No 90, de 21 de janeiro de 1980. A pesquisa, de natureza qualitativa, esteve ancorada pelos preceitos da História Cultural, sob referenciais de Pesavento (2014) e Chartier (1990; 1991). Para a construção da História das Disciplinas Escolares, utilizaram-se como referencial Chervel (1990) e Viñao (2008). A opção metodológica pautou-se na História Oral, pois permite ao pesquisador e pesquisado (re)significar a subjetividade encontrada por trás de cada palavra, apoiando-se em estudiosos como Alberti (2013), Portelli (2016) e Meihy e Barbosa (2019). Para composição do corpus empírico, as fontes documentais foram obtidas a partir de consultas ao Instituto de Memória Histórica e Cultural (IMHC) da UCS, e as entrevistas com os licenciados, que totalizaram dez, apoiaram-se em roteiro previamente definido. Das entrevistas, originaram-se as categorias e subcategorias, as quais foram analisadas sob a ótica da Análise de Conteúdo, proposta por Roque Moraes (1999; 2003). Destacaram-se três que tiveram maior relevância nas falas: contribuições e saberes advindos da licenciatura; disciplinas e metodologias utilizadas em sala de aula; a licenciatura com permissão de registro profissional junto ao MEC, a "carteirinha de professor". A fundamentação teórica para as categorias foi baseada em Tardif (2014) e Tardif e Lessard (2014), com a explanação dos saberes profissionais e práticas docentes; Anastasiou e Alves (2015), com os pressupostos para as estratégias do trabalho em sala de aula; e Nóvoa (1995; 1999; 2009; 2011), com a aprendizagem docente e o desenvolvimento profissional dos professores. O estudo permitiu que fossem discutidos os fundamentos históricos da formação do profissional da enfermagem no ensino superior, além da explanação e análise sobre os objetivos e as propostas dos projetos político-pedagógicos. Dessa forma, o trabalho permitiu a compreensão de que a enfermagem possui, desde os primórdios de sua criação como profissão, o cuidado como instrumento de trabalho, mas sempre atrelado às questões ligadas à educação. Assim, entende-se que foi possível contemplar a proposta inicial da pesquisa, pois, além do acesso às fontes documentais, houve um esforço considerável do pesquisador de construir uma narrativa possível sobre a história do curso de Licenciatura em Enfermagem na UCS, por meio das memórias de quem as vivenciou. [resumo fornecido pelo autor]
Keywords: Universidade de Caxias do Sul. Campus Universitário de Caxias do Sul. Curso de Enfermagem - História; Educação - História; Memória coletiva; Professores - Formação; University of Caxias do Sul. University Campus of Caxias do Sul. Nursing Course - History; Education - History; Collective memory; Teachers, Training of